2021
DOI: 10.1021/acsami.1c09394
|View full text |Cite
|
Sign up to set email alerts
|

Studying and Utilizing Traditional Technologies: Microstructure and Formation Mechanism of ε-Fe2O3 on Traditional Japanese Bizen Stoneware

Abstract: Traditional Japanese Bizen stoneware is produced by firing a specific type of green clay in a wood-fired kiln at approximately 1200 °C. During this process, single crystalline branched dendrite-like particles of Al-substituted ε-Fe2O3 (ε-Fe1.7Al0.3O3) with widths and lengths of approximately 15 and 30 μm, respectively, are formed on the surface of the ceramic. Composite particles consisting of ε-Fe2O3 epitaxially connected to spinel structure compounds [comprising the Fe-substituted spinel (Mg,Fe)­(Al,Fe)2O4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…These diagrams and the ED patterns in Figure a indicate that the crystallographic relationship between the ε-Fe 2 O 3 and the spinel structure compound was a ε // [112̅] s , b ε // [1̅10] s , and c ε // [111] s , where the indices ε and s indicate the ε-Fe 2 O 3 and spinel structure compound, respectively. This crystallographic relationship is consistent with that previously determined in the case of particles formed in Bizen stoneware …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These diagrams and the ED patterns in Figure a indicate that the crystallographic relationship between the ε-Fe 2 O 3 and the spinel structure compound was a ε // [112̅] s , b ε // [1̅10] s , and c ε // [111] s , where the indices ε and s indicate the ε-Fe 2 O 3 and spinel structure compound, respectively. This crystallographic relationship is consistent with that previously determined in the case of particles formed in Bizen stoneware …”
Section: Resultsmentioning
confidence: 99%
“…Our group has studied the application of traditional techniques, such as the process by which colors are applied to Japanese ceramics, with the aim of transitioning these same methods to the production of industrial materials. , In prior examinations of Bizen stoneware having a silvery luster, we found composite particles consisting of ε-Fe 2 O 3 and a spinel structure compound in the Mg–Al–Fe–O system. Iron­(III) oxide, typically referred to as Fe 2 O 3 , has four polymorphs: α-, β-, γ-, and ε-Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to the latest study, Al-substituted ε-Fe 2 O 3 was also found on a Japanese Bizen stoneware replica, which is widely believed to be profoundly influenced by Chinese high-fired black-glazed tea cups. 29…”
Section: Al Doping Was Discovered In ε-Fe 2 O 3 Lattices On Hare's Fu...mentioning
confidence: 99%
“…Epsilon iron oxide (ε-Fe 2 O 3 ) nanomagnets are receiving attention due to their large magnetic coercivity and high-frequency millimeter wave absorption at 182 GHz. 17–37 Additionally, metal-substituted ε-Fe 2 O 3 (ε- M x Fe 2− x O 3 ) exhibits zero-field ferromagnetic resonance over a wide frequency range of 35–222 GHz. 38–50 ε- M x Fe 2− x O 3 has entered the market as a millimeter wave absorber due to these useful properties.…”
Section: Introductionmentioning
confidence: 99%